Highly Stretchable and Sensitive Strain Sensor based on Ionogel/Ag Synergistic Conductive Network. Issue 11 (9th February 2022) - Sun, Jingxian; Yuan, Yixin; Lu, Guoqiang; Xue, Tanlong; Nie, Jun; Lu, Yan
Abstract: Recently, flexible strain sensors have been intensively studied in order to meet the growing demands of detecting multiscale mechanical deformations. However, it remains a big challenge to integrate high stretchability and high sensitivity in a strain sensor simultaneously. In this study, a highly stretchable and sensitive strain sensor is successfully fabricated by constructing ionogel/silver synergistic conductive network. The transmetalation reaction is utilized to transform the copper atoms in the copper/ionogel nanocomposite into more silver atoms with larger radius, which eliminates the interspace among the nanoparticles, and therefore a silver/ionogel nanocomposite with high conductivity is obtained. Owing to the fragility of the conductive network, the obtained nanocomposite possesses high sensitivity. In addition, as the polymer substrate, the conductive ionogel can connect the crack of the silver conductive network during stretching, endowing the nanocomposite with high stretchability. Hence, the obtained strain sensor exhibits a high sensitivity in a wide sensing range and can detect various human activities. Therefore, this strategy can be envisioned as promising strategy for fabricating high‐performance strain sensors and other flexible electronics. Abstract : A nanocomposite‐based strain sensor with Ag/ionogel synergistic conductive network is prepared by constructing copper–silver transmetalation reaction in ionogel. The obtained strain sensor possesses both high sensitivity and high stretchability, and can detect different mechanical deformation, such as human joint motions and pulse.